Interaksionisme Simbolik Ritual Meron di Indonesia dan Relevansinya dalam al Quran - Atabik, Ahmad (FIKRAH, 2020)
This paper examines the cultural traditions of meron in Pati Indonesia. A tradition that is interpreted with respect to the prophet by bringing a cone made from large rengginang. The method used is qualitative research with an ethnographic approach that aims to find out the meaning of each meron symbol. The theory used is Herbert Blumer's symbolic interactionism that narrates three assumptions of symbols, namely meaning as the basis of human action, meaning created from social interaction and meaning modified through reader interpretation. The results of this paper are that the meron tradition has relevance to the teachings of Islam as a form of da'wah. Rengginang as a symbol of gratitude and togetherness, a mosque as a religious symbol and the arrangement of rengginang is a symbol of the levels of Iman, Islam and Ihsan. The relevance of meron to the verses of the Quran, as in the study of QS. al-Baqarah: 260. Rengginang made from rice is hinted at in QS. al-Baqarah: 261 and QS. Al-Fath: 29. While the mosque symbol is strengthened in the QS. At-Taubah: 18-19.